WAYS TO SOLVE TAX BURDEN OPTIMIZATION THROUGH FOREIGN EXPERIENCE AND EXPERIENCE TESTING IN COUNTRIES - Samadov , Shakhrukh (Science technology&Digital finance, 2024)
Consistent reduction of the tax burden, simplification of the taxation system and improvement of tax administration are the most important conditions for the rapid development of the economy and improvement of the investment attractiveness of the country. At the same time, there are a number of systemic problems in this area, the results of which prevent a single increase in economic growth, increased business and investment activity, the formation of a healthy competitive environment, as well as the provision of the required level of tax and other mandatory fee aggregation. In the process of determining the tax burden in foreign countries, especially in developed countries, as well as analyzing this indicator, ways are indicated to study the factors affecting the level of tax burden, taking into account the specific aspects of the tax systems of foreign countries.